Exploring the optimal factor structure of mind-wandering: Associations with neuroticism. - Joseph Diehl; Nicolas Camacho; Moria Smoski (PLoS ONE)
Mind-wandering is an essential cognitive process in which people engage for 30-50% of their waking day and is highly associated with neuroticism. The current study identified the factor structure of retrospective self-report items related to mind-wandering and perseverative cognition content and explored these associations with neuroticism. In an adult community sample (N = 309), items from the NYC Cognition Questionnaire, the Penn State Worry Questionnaire Short Form, and the Rumination Responses Brooding Subscale were entered into factor analyses to test the optimal factor structure of these items. We employed a structural model to investigate associations of mind-wandering facets with neuroticism. A correlated three factor solution best fit the data (CFI = .94, TLI = .93, SRMR = .07, RMSEA = .07). Bifactor models failed to provide evidence for a general mind-wandering construct above and beyond variance explained by mind-wandering and perseverative cognition facets. The structural model revealed differential associations of each facet with neuroticism. A wandering mind is not always an unhappy mind. Whereas worry and rumination are associated with higher levels of neuroticism, mind-wandering has other components that relate to positively valenced cognition and lower neuroticism. Adaptive and maladaptive mind-wandering should be tested together in future studies of personality and psychopathology.